Innovations From 'Down-Under': A Focus on Prescription to Non-Prescription Medicine Reclassification in New Zealand and Australia - Gauld, N.; Kelly, F.; Emmerton, Lynne; Bryant, L.; Buetows, S. (SansSerif Publishing, 2012)
Background: Australia and New Zealand (NZ) contribute to the international trend of medicines reclassification from prescription to non-prescription availability (switch). Both countries have been acknowledged as being as advanced or even more so than the United Kingdom (UK) in availability of medicines without prescription, despite not making some of the recent innovative UK switches. Objective: To derive a measure of progressiveness in switch; to compare the progressiveness of switch between NZ and Australia; and to compare NZ and Australia switch activity with the UK. Methods: Records of medicines classification meetings in Australia and NZ from 2000 to 2011 were analysed with respect to all switch considerations (whether approved or not approved). Switches in Australia and NZ were compared with those in the UK. A new measure, ‘innovative switches’, was developed to provide a useful measure of switch progress. Results: Australia demonstrated ‘switch innovation’ in the early 2000s, including the ‘first-in-world’ switch of orlistat, but has slowed down since. Recently NZ has become more innovative than Australia with first-in-world switches of oseltamivir, famciclovir and calcipotriol. Switches driven by sponsors, and also non-sponsors, and exemption to prescription supply have facilitated consumer access to medicines in NZ. However, medicines that were switched in the UK but not Australasia indicate locality-specific barriers. Conclusions: Australia and NZ have both been progressive with medicines reclassification in the past 12 years, albeit with fewer innovative switches in Australia recently. NZ has become more innovative since 2004 and is now one of the more progressive countries in this trend. Our ‘innovative switch’ framework demonstrates potential for ongoing monitoring of international developments.